Scientific Socialism: The Case of Robert Owen - Leopold, D (Routledge, 2015)
At the same time, the contributors of this volume take up the theme of how particular ideas such as political wisdom and political leadership as well as the nature of political science itself have been addressed in the history of Western political philosophy—that is, in what ways the elements that constitute statesmanship have over the centuries undergone several transformations and ramifications to fit within certain contexts and historical developments. Hence, the volume neither ...